Nardostachys Jatamansi DC: A Medicinal Treasure in Peril(A Review) - Preethi, Preethi; Sumathy, G.; Venkatalakshmi, Venkatalakshmi (Journal of Neonatal Surgery, 2025)
The miraculous but endangered plant, Nardostachys Jatamansi DC is a highly medicinal value, primitive, and therapeutic herbal plant used in both daily self-care and professionally managed health care. It is an endangered species due to overexploitation of its rhizomes for medicinal, aromatic uses, folk medicine, overgrazing, loss of habitats, and forest degradation. All the parts of the plants are used for various therapeutic activities like Alzheimer’s, anti-convulsion, antioxidants, hair growth, hepatoprotective, Parkinson’s, etc. Phytosterols, terpenoids, flavonoids, and phenolic compounds present in Nardostachys Jatamansi have strong pharmacological properties because they are bioactive molecules. The review focuses on describing the biological activities of these natural products; therefore, there is potential for their application in disease prevention and treatment. Phytosterols, consisting of beta-sterols, are cardioprotective, anti-inflammatory, antimicrobial, and anticancer agents, especially with regard to apoptosis in cancerous breast cells. Triterpenoids, including lupeol and ursolic acid, confer neuroprotection, anxiolysis, antioxidation, and anti-inflammation. Saponins are a subclass of triterpene glycosides that increase the immune response and protect against lipidemia. Furthermore, n-hexacosanol has been identified as an agent with antimicrobial, antioxidant, and hepatoprotective activities. Flavonoids and phenolic compounds are renowned for their significant antioxidant and anti-inflammatory activities. Anti-cancer and free radical scavenging capabilities make flavones, flavonols, and flavonones effective. Through antimicrobial activity and neuroprotection, gallic acid and protocatechic acid of the phenolic acids showed chemoprevention. Chlorogenic and ferulic acids have potential applications in seizure management, cardiovascular health, and protection of skin. On the other hand, syringic acid is a phenolic derivative with great antioxidant potential. These compounds are of significant interest in drug development and nutraceutical applications because of their diversified bioactivity. Their natural origin and multifaceted pharmacological properties offer a safer alternative to synthetic drugs. Further research into their mechanisms of action, bioavailability, and synergistic effects may open the doors to novel therapeutic strategies in the management of chronic diseases. This review compiles existing scientific findings, offering insight into the potential health benefits and applications of phytosterols, terpenoids, flavonoids, and phenolic compounds.